Analysis of Learning Methods Among Students in Adopting Education 4.0 at Higher Learning Institution in Johor - ZULKIPLI, HAFIZAH (Research in Management of Technology and Business, 2023)
Education 4.0 promotes education in a novel way, primarily through the use of technology-based tools and resources. However, education in Malaysia still lacks of exposure in terms of IoT to students and educators. Therefore, this study aims to determine the level of learning methods among students in adopting education 4.0. It’s also aims to determine the level performance in adopting education 4.0 among students and to determine the relationship between learning methods in adopting education 4.0 and performance in adopting education 4.0 among students will be focused on University Tun Hussein Onn Malaysia and University Technology Malaysia. The data obtained will be analyzed descriptively and correlation using Statistical Package for Science (SPSS) and Microsoft Excel. This study used online survey questionnaire to collect the data from 271 valid respondents. The results show that the level of learning methods influence to performance in adopting education 4.0 among students in UTHM and UTM, because when learning methods increase, then the performance in adopting education 4.0 also increase.